Functional outcomes of arthroscopic transosseous rotator cuff repair using a 2-mm tape suture in a 137-patient cohort - Jean-Étienne Beauchamp; Marc Beauchamp, MD, FRCSC (JSES International, 2021)
Background: Although being the historical gold standard for rotator cuff repair, open transosseous (TO) repair was largely replaced by anchor-based methods with the advent of arthroscopic surgery owing to their comparative ease of use. However, suture anchors are at risk of dislodgement, especially among older patients, who have more osteopenic bone or those presenting large tears. Considering the ever-increasing active life expectancy and associated increased quality of life expectations by older generations, the need to offer safe and efficient surgical treatments to these patients imposes itself. Arthroscopic TO repairs would combine the best of both worlds and be well adapted to these populations. The primary objective of this study was to evaluate the functional outcome and complication rate of the TO arthroscopic repair technique when using a 2-mm braided suture tape. The secondary objective of this study was to assess functional outcome of TO repair in older patients and patients with >3-cm tears. Methods: One hundred thirty-seven consecutive patients with full-thickness rotator cuff tear who underwent arthroscopic TO (anchorless) rotator cuff repair between January 2011 and December 2013 were reviewed. The surgery was performed by a single surgeon with a reusable curved suture passer and 2-mm braided tape suture. Follow-up was 3 to 5 years (mean = 50 months). All patients underwent preoperative and postoperative functional assessments (American Shoulder and Elbow Surgeons and Quick Dash) and were questioned with their overall satisfaction. Results: Thirty-eight (28%) of the 137 patients were 65 years and older, and 62 (45%) had a large or massive tear. One patient (0.7%) had early retear at the suture-tendon interface after trauma 3 weeks postoperatively. The average Quick Dash score improved by 55.6 points and the average American Shoulder and Elbow Surgeons score improved by 69.7 points 3.5 and 6.3 times their minimal clinically important differences, respectively. There was no significant difference in final functional outcomes between patients 65 years and older and younger patients or between patients with large and massive (>3 cm) and smaller tears (≤3 cm). Mean operative time was 68 min ± 16. Conclusions: Arthroscopic TO repair using a 2-mm tape material has achieved significant mid-term functional improvement, with results statistically unaffected by larger tear size (>3 cm) or older age (≥65 years).